PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Consumer Goods Yang Terdaftar di BEI tahun 2017-2022) - Prasetya, Muhammad Ilham; Mutmainah, Siti (Diponegoro Journal of Accounting, 2024)
The development of consumer goods companies in Indonesia has resulted in widespread tax evasion or tax avoidance by companies. Corporate Social Responsibility is one way that companies can use to practice tax avoidance. This research aims to determine the effect of Corporate Social Responsibility on tax avoidance. The independent variable in this research is Corporate Social Responsibility. Meanwhile, the dependent variables used are tax avoidance and ownership structure as moderating variables.The population in this study used consumer goods companies listed on the Indonesia Stock Exchange (BEI) in 2017-2022. The research sample was determined using the Purposive Sampling Method. In accordance with predetermined criteria, 28 companies were produced with 3 (three) years of observation. The final sample used in this research was 168. This research used Multiple Linear Regression Analysis with the SPSS 25 application.The results of this research show that Corporate Social Responsibility influences tax avoidance, managerial ownership weakens the relationship between Corporate Social Responsibility and tax avoidance, institutional ownership weakens the relationship between Corporate Social Responsibility and tax avoidance.